TINJAUAN YURIDIS TERHADAP ANAK KORBAN KEKERASAN SEKSUAL DALAM LINGKUNGAN KELUARGA MENURUT UNDANG-UNDANG NOMOR 35 TAHUN 2014 - Wahyuni, Sri; Hibar, Ujang; Samudra, Dian (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2024)
Sexual violence is a case that often occurs and continues to increase every year. The victims of this crime are not adults but children who still need a lot of love and attention from their families and society. This research aims to determine the factors that cause sexual violence in the family environment and to find out the legal provisions regarding sexual violence against children in the family environment according to positive law. The research method used is empirical legal research, which looks at conditions and facts in society from interviews and literature studies as well as direct observation to obtain a complete and complete picture. The results of the research on the factors that influence the occurrence of sexual violence against children in the family environment are low education and economic factors, environmental factors and residence, factors of lack of understanding of the law, factors of lack of understanding of religion, factors of drinking (alcohol) and factors of the role of victims and legal provisions regarding sexual violence against children in the family environment according to positive law in Law Number 35 of 2014 concerning Child Protection. With this research, it is hoped that the National Commission for Child Protection in Banten Province will be even more active in preventing sexual violence against children, and it is also necessary to conduct outreach to areas that are far from the reach of the public in order to foster community or family awareness in preventing sexual violence against children in the family environment.